Parenteral Antiplatelet Drugs in ST-Elevation Myocardial Infarction: Current Status and Future Directions - Rikken, Sem A. O. F.; Storey, Robert F.; Andreotti, Felicita; Clemmensen, Peter; ten Berg, Jurriën M. (Thrombosis and Haemostasis, 2022)
Oral inhibitors of the platelet P2Y12 receptor are indispensable in the treatment of ST-elevation myocardial infarction (STEMI), improving outcomes and even reducing mortality in some studies. However, these drugs are limited by delayed absorption and suboptimal platelet inhibition at the time of primary percutaneous coronary intervention. Despite efforts to achieve faster and more sustained platelet inhibition, strategies such as prehospital administration, higher loading doses, and crushed formulations have not led to improved coronary reperfusion. Parenteral glycoprotein IIb/IIIa inhibitors act sooner and are more potent than oral P2Y12 inhibitors, but their use has been limited by the increased risk of major bleeding and thrombocytopenia. Hence, there is a clinical need to refine drugs that deliver rapid, effective, yet safe platelet inhibition in the setting of STEMI. Novel parenteral antiplatelet drugs, such as cangrelor, selatogrel, and zalunfiban, have been recently developed to achieve rapid, potent antiplatelet effects while preserving hemostasis. We provide a description of currently available parenteral antiplatelet agents and of those in clinical development for prehospital administration in STEMI patients.
Keywords: prehospital administration; antiplatelet drugs; ST-elevation myocardial infarction; cangrelor; selatogrel; zalunfiban